THE INFLUENCE OF PERCEIVED VALUE AND BRAND EXPERIENCE ON BRAND LOYALTY IN DANA APPLICATION USERS: (Study on Dana Users in Simalungun) - Janwar Cristopan Purba; Nicholas Marpaung (Transpublika Publisher, 2022)
This research aims to determine how the effect of perceived value and brand experience on brand loyalty partially and simultaneously on DANA application users in Simalungun. This research uses quantitative research with an associative approach. The population in this study are users of the DANA application in Simalungun. Sampling was done by purposive sampling technique using 100 respondents as the research sample. Primary data in this study were obtained from distributing questionnaires through a google form, and secondary data were obtained through a literature study. The analytical method used is the validity test, classical assumption test, reliability test, multiple linear regression analysis, and hypothesis testing. The results showed that the perceived value variable (X1) and the brand experience variable (X2) partially had a significant effect on brand loyalty. Based on the coefficient of determination test, the R2 value is 0.462, which means the effect of perceived value and brand experience on brand loyalty of DANA application users in Simalungun is 46.2% while the remaining 53.8% is influenced by other factors not explained in this work.